Psychosocial Approach to the Effect of Stress on Performance in the Workplace - Bennamate, Safa; Bouazzaoui, Ahmed El (Journal of Science & Technology, 2023)
Our study aimed to investigate the effect of the interaction between stress perception and its intensity on performance in a professional context. We conducted a series of analyses to determine whether the way individuals perceive stress or the level of stress intensity plays a predominant role in determining workplace performance. Following the study results, we did not observe an interaction between stress perception and its intensity. However, participants who perceived stress as a challenge to overcome displayed higher levels of performance, while those who viewed stress as a threat to avoid had significantly lower performance levels, regardless of the perceived stress intensity. This observation underscores the significance of how individuals interpret stressful situations in the workplace. These findings have significant implications for managers, employees, and human resources professionals. They suggest that stress management in the workplace should focus on promoting a positive perception of stress as a challenge, which could enhance optimal performance. Ultimately, our study contributes to shedding light on the intricate relationship between stress perception, its intensity, and workplace performance, highlighting the potential of a positive stress perception to improve professional outcomes.
Keywords: Transactional model; optimal functioning zone; stress; appraisal; Performance